2016
DOI: 10.1007/s40596-016-0526-y
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Sleep and Exercise Associated with Burnout and Depression Among Medical Students

Abstract: Sleep habits, exercise, and a positive depression screen were associated with burnout risk within the medical student population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
131
1
18

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 23 publications
17
131
1
18
Order By: Relevance
“…In the current study we found sleep deficit also increases risk of burnout. Firefighters with daytime sleepiness were at 2.5‐, 2.1‐ and 1.2‐fold risk of high EE, high DP and low PA, respectively, which is consistent with medical students (Wolf & Rosenstock, ). A similar association between sleepiness and burnout was found in patients with OSA, but only for EE and DP (Guglielmi, Jurado‐Gamez, Gude, & Buela‐Casal, ).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the current study we found sleep deficit also increases risk of burnout. Firefighters with daytime sleepiness were at 2.5‐, 2.1‐ and 1.2‐fold risk of high EE, high DP and low PA, respectively, which is consistent with medical students (Wolf & Rosenstock, ). A similar association between sleepiness and burnout was found in patients with OSA, but only for EE and DP (Guglielmi, Jurado‐Gamez, Gude, & Buela‐Casal, ).…”
Section: Discussionsupporting
confidence: 78%
“…Firefighters are sometimes permitted to sleep while on-duty overnight, but these sleep opportunities are often disrupted, especially in personnel with sleep disorders (Jay, Smith, Windler, Dorrian, & Ferguson, 2016) or mental health conditions (Hom et al, 2016). Sleep and mental health conditions have been associated with burnout in occupations involving night work (Katsavouni et al, 2016;Kousloglou et al, 2014;Rajaratnam et al, 2011;Wolf & Rosenstock, 2017), and incomplete recovery from work demands, potentially in the form of short sleep, has been identified as a possible mediating factor in the development of burnout (Gluschkoff et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…4,[15][16][17][18] Clinicians working rotating shifts, night shifts, or shifts of more than 12 hours may experience diminished cognitive and physical functioning, 8 decreased job satisfaction, 20,21 and poorer quality of life, 8,22 and they are at an increased risk for professional burnout. 23,24 These clinicians also report experiencing chronic fatigue, 21,22 cardiac symptoms, 21 decreased motor skills, 8 and negative psychological symptoms such as depression. 22 Personal well-being and client safety are negatively affected because of poorer clinician sleep quality and quantity, 21 as poor sleep is associated with higher risks of medical errors, 25,26 motor vehicle accidents, 8,22 and needlestick injuries.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the survey answers by the residents, the authors articulated potential interventions (e.g., more time for work-life balance) that remain to be tested empirically. Similarly, Wolf and Rosenstock [5] surveyed medical students online, assessing sleep and exercise and administering Maslach burnout inventory assessments. Burnout correlated with Epworth sleepiness scale's "pathological sleepiness," less than 7 h of sleep per night, and a positive depression screen.…”
mentioning
confidence: 99%